Pengaruh Bauran Pemasaran Syariah Terhadap Keputusan Pembelian Handphone Di Toko Surya Phone Samarinda - Marisa Ayu Ningsih; Norvadewi Norvadewi; Anwaril Hamidy (Borneo Islamic Finance and Economics Journal, 2021)
Surya Phone's relationship with the sharia marketing mix can be seen from the price of Surya Phone in determining the price determination based on the value or price of a product that follows the cellphone market in Samarinda and the clarity of the prices listed in the store, not only the profit that is made in the market. own Surya Phone. In terms of promotion, Surya Phone also conveys clear information about the products being promoted to potential consumers or customers, there is no element of fraud or mere lies. The quality of the product that will be marketed by Surya Phone is also clearly agreed upon by both parties, between the seller and the buyer of the product. Thus, various efforts are certainly made by the Surya Phone store to be able to improve product quality, price, place and promotion so that purchasing decisions by customers can also improve. This study aims to determine the effect of the Islamic marketing mix on the decision to purchase mobile phones at Surya Phone.The method used in this study is a quantitative method. The type of research used in this scientific work is associative research. The number of samples used in this study were 100 customers at the Surya Phone Samarinda store. The technique used in sampling is incidental sampling. Data collection techniques with questionnaires. The analytical method used in this research is multiple regression analysis. The results of this study indicate that partially the product has no significant effect on the decision to purchase cellphones at the Surya Phone store, the price has a significant effect on the decision to purchase cellphones at the Surya Phone store, the place has a significant effect on the decision to purchase cellphones at the Surya Phone store, and promotions have no significant effect on the purchase decision. decision to purchase mobile phones at the Surya Phone store. Simultaneously, the product, price, place, and promotion variables have a significant effect on the decision to purchase cellphones at the Surya Phone store.